Brain Death as the End of a Human Organism as a Self-moving Whole. Issue 5 (1st October 2021) - Omelianchuk, Adam
Abstract: The biophilosophic justification for the idea that "brain death" (or total brain failure) is death needs to support two claims: (1) that what dies in human death is a human organism, not merely a psychological entity distinct from it; (2) that total brain failure signifies the end of the human organism as a whole. Defenders of brain death typically assume without argument that the first claim is true and argue for the second by defending the "integrative unity" rationale. Yet the integrative unity rationale has fallen on hard times. In this article, I give reasons for why we should think of ourselves as organisms, and why the "fundamental work" rationale put forward by the 2008 President's Council is better than the integrative unity rationale, despite persistent objections to it.